Improving Provider Communication about HPV Vaccines for Vaccine-Hesitant Parents Through the Use of Motivational Interviewing. Issue 4 (3rd April 2018) - Reno, Jenna E.; O'Leary, Sean; Garrett, Kathleen; Pyrzanowski, Jennifer; Lockhart, Steven; Campagna, Elizabeth; Barnard, Juliana; Dempsey, Amanda F.
Abstract : Human papillomavirus (HPV) vaccine uptake is below that of other routine adolescent vaccines. This is due in part to the fact that the HPV vaccine is often not routinely recommended by providers to all eligible adolescents. While providers' recommendations are crucial, even a strongly stated recommendation can be insufficient among HPV vaccine-hesitant parents. Providers must be prepared to respond to parental concerns following giving the recommendation for the HPV vaccine. This paper presents the analysis of implementation of an intervention aimed at improving provider communication with HPV vaccine-hesitant parents. Healthcare providers and staff at eight pediatric and family medicine clinics received communication training that included motivational interviewing (MI) techniques. Process evaluation in the form of serial surveys, as well as program evaluation in the form of focus groups with participating providers and staff, assessed the perceived efficacy of the intervention. Outcomes included time spent discussing the HPV vaccine during clinical visits, providers' self-efficacy for addressing parental HPV vaccine hesitancy, and their general perceptions of the effectiveness of MI techniques. Overall, findings indicate the intervention improved providers' communication with HPV vaccine-hesitant parents and providers reported the use of MI played a central role in improved HPV vaccine acceptance. Lessons learned and recommendations for future interventions are also discussed.